Pulmonary Vascular Resistance Measurement Remains Keystone in Congenital Heart Disease Management - Tamimi, Omar; Mohammed, Mohammed H. A. (Frontiers in Cardiovascular Medicine, 2021)
Pulmonary vascular resistance (PVR) plays a major rule in congenital heart management and critical decision. The impact of pulmonary vascular disease in the early and late morbidity and mortality after cardiac surgery and interventional catheterization in congenital heart defect (CHD) highlights the importance of critical evaluation for PVR. Currently, PVR is evaluated with invasive cardiac catheterization for hemodynamic data collection, processing and analysis. Despite the limitation of hemodynamic evaluation in the setting of CHD, accurate data analysis and interpretation have significant impact on clinical outcome and procedure success. This article reviews the basic of calculation of Pulmonary Vascular Resistance in the setting of congenital heart disease with diagrammatic illustration for easy understanding of the hemodynamic.